THE PROFILE OF CHILDREN WITH CONGENITAL RUBELLA SYNDROME SUFFERING FROM HEARING DISORDERS IN DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA - Raudhatuzzahra Kesuma; Haris Mayagung Ekorini; Tri Hartini Yuliawati (Universitas Airlangga, Surabaya, Indonesia, 2020)
Background: Congenital Rubella Syndrome (CRS) is an infection that can cause hearing loss which is commonly found in infants in Indonesia. The hearing screening of otoacoustic emission (OAE) and automated auditory brainstem response (AABR) is essential as an early screening to prevent speech and language development disorders which may reduce the social function of the patient in the future. Objective: To analyze the profile of children with CRS who suffer from hearing loss in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia in 2015-2017. Materials and Methods: This research employed a descriptive retrospective study by collecting 118 secondary data from the medical records. Results: CRS was mostly found in 0-3 months age group (76 patients), and was dominated by males (62 patients). The most common signs and symptoms were congenital heart disease (49 patients), followed by hearing loss (37 patients). The serological results were mostly dominated by negative IgM and positive IgG (40 patients). The most dominant results of hearing screening test were OAE and AABR bilateral refer (45 patients). Conclusion: The profile of children with CRS suffering from hearing loss is various, depending on which country the research is conducted.